Faktor FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN - IRBAH NURJIHAN; Hendra Hendra (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study aims to examine the factors that influence firm value. The independent variables in this research consist of firm size, capital structure, firm growth, investment decisions, and dividend policy. The object of this research are food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2010 to 2019. This research used 60 samples and the sample selection procedure used was purposive sampling method. The research test used multiple regression analysis. The results of this research indicate that the variables of firm size, capital structure and firm growth have no effect on firm value. Meanwhile, the investment decision variables and dividend policy have an influence on firm value. Investment decisions that have a positive effect on firm value indicate that investors have high expectations of the company's potential market value. Dividend policy that has a negative effect on firm value indicates that low dividends will cause the company's internal funds to increase so that the company's performance also increases which results in an increase in firm value.